2001
DOI: 10.1046/j.1365-2958.2001.02608.x
|View full text |Cite
|
Sign up to set email alerts
|

Sites of positive and negative regulation in the Bacillus subtilis antiterminators LicT and SacY

Abstract: The Bacillus subtilis homologous transcriptional antiterminators LicT and SacY control the inducible expression of genes involved in aryl β‐glucoside and sucrose utilization respectively. Their RNA‐binding activity is carried by the N‐terminal domain (CAT), and is regulated by two similar C‐terminal domains (PRD1 and PRD2), which are the targets of phosphorylation reactions catalysed by the phosphoenolpyruvate: sugar phosphotransferase system (PTS). In the absence of the corresponding inducer, LicT is inactiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
84
0
9

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(98 citation statements)
references
References 50 publications
5
84
0
9
Order By: Relevance
“…In this case it was concluded that the conserved His-208 residue in PRD2 is the target of negatively acting phosphorylation by EII Bgl (26). Thus, no general rules appear to exist concerning the molecular mechanisms governing the regulation of this protein family (8,20).…”
mentioning
confidence: 97%
See 3 more Smart Citations
“…In this case it was concluded that the conserved His-208 residue in PRD2 is the target of negatively acting phosphorylation by EII Bgl (26). Thus, no general rules appear to exist concerning the molecular mechanisms governing the regulation of this protein family (8,20).…”
mentioning
confidence: 97%
“…Where investigated, the first conserved histidine in PRD1 was found to be crucial for negative control. Exchange of this histidine leads to constitutively high antitermination activity in vivo even in the absence of the specific substrate (20,24,25). The second histidine in PRD1 participates in negative control of LicT and LacT (20,25).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, for BglG and LevR, the enzyme II-mediated inhibition process seems to rely on the presence of a negative charge on a conserved histidine in PRD2. In contrast, the site suggested for the phosphorylation of LicT and SacY by their respective enzymes II, BglP and SacX, is a conserved histidine in PRD1 (29,31). Hence, the site on which the antiterminators are phosphorylated by their cognate enzymes II seems to be a conserved histidine in either PRD1 or PRD2.…”
Section: Fig 3 Spr Analysis Of the Interaction Between The Prd Domamentioning
confidence: 93%